Herculean labours: Erasmus and the editing of St. Jerome's letters in the Renaissance - Pabel, Hilmar M. (Library of the written word, 2008)
Jerome in print, 1467-1600 -- Classifying Jerome -- Portraying Jerome -- Elucidating Jerome